2010
DOI: 10.1002/ccd.22458
|View full text |Cite
|
Sign up to set email alerts
|

Distal stent delivery with guideliner catheter: First in man experience

Abstract: Failure to deliver stents is one of the commonest causes of procedural failure in contemporary PCI practice. We describe successful use of the Guideliner catheter, the first purpose designed FDA and CE marked device delivery catheter in 13 complex cases in native coronary vessels and bypass grafts performed via the radial route to enable distal stent delivery following failure of conventional techniques. We discuss how the Guideliner catheter may be used to facilitate difficult radial cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 16 publications
5
73
0
Order By: Relevance
“…[6][7][8][9] . The GuideLiner (GL) catheter (Figure 1) is a novel rapid exchange guide catheter extension system that provides active guide support by its 20 cm-long flexible tubular end, which can be deeply advanced into target vessels [10][11][12][13][14][15][16][17][18] . Its handling is particularly easy, as it is does not require disconnection of the haemostatic valve at the proximal end of the guide catheter and is compatible with standard 180 cm-long guidewires.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9] . The GuideLiner (GL) catheter (Figure 1) is a novel rapid exchange guide catheter extension system that provides active guide support by its 20 cm-long flexible tubular end, which can be deeply advanced into target vessels [10][11][12][13][14][15][16][17][18] . Its handling is particularly easy, as it is does not require disconnection of the haemostatic valve at the proximal end of the guide catheter and is compatible with standard 180 cm-long guidewires.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a limited number of reports and case series have been published on the GL guide catheter extension [10][11][12][13][14][15][16][17][18] . Mamas et al reported a case series of 13 complex coronary interventions, performed via the radial artery with the "5-in-6" Fr GL system 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, descriptions of its successful use in venous grafts. 2,3 Furthermore, it is recommended, as a precaution, not to introduce the catheter more than 10 cm beyond the tip, as the GuideLiner TM can get stuck in the guide catheter (generally in the second curvature of the catheter). An intubation beyond 20 cm completely externalises the tube with the metal collar to the vessel, causing severe damage.…”
Section: A D E F B Cmentioning
confidence: 99%
“…This technique is an alternative to single-catheter deep intubation and nowadays it can be performed with specific devices including Guideliner (Vascular Solutions Inc.) or the Guidezila (Boston Scientific Corporation) [9]. It has been useful in complex cases [10] and can yield excellent results, particularly in emergent situations requiring covered stent implantation.…”
mentioning
confidence: 99%